Effectiveness of the diode laser in the treatment of ligature-induced periodontitis in rats: a histopathological, histometric, and immunohistochemical study - Theodoro, Letícia Helena [UNESP]; Caiado, Roberto Coelho; Longo, Mariellen [UNESP]; Noronha Novaes, Vivian Cristina [UNESP]; Zanini, Naida Assem [UNESP]; Ervolino, Edilson [UNESP]; Almeida, Juliano Milanezi de [UNESP]; Garcia, Valdir Gouveia [UNESP] (Springer, 2015)
The aim of this study was to evaluate the effects of the use of a high-power gallium-aluminum-arsenide diode laser (GaAlAs; 808 nm, 1 W, 20 s, 20 Hz, 10 J) alone or as adjunctive therapy to scaling and root planing in the treatment of induced periodontitis in rats. Periodontitis was induced by placing a ligature around the mandibular first molar of 60 rats. After 7 days, the ligature was removed and the animals were divided into four groups as follows: C (control), no periodontal treatment; SRP, scaling and root planing (SRP); DL, diode laser (DL) irradiation treatment; and SRP/DL, both SRP and DL irradiation treatment. Five animals from each group were euthanized at 7, 15, and 30 days posttreatment. The effectiveness of the treatments was evaluated in the furcation area using histopathological analysis, histometric analysis of alveolar bone loss (ABL), and immunohistochemical detection of tartrate-resistant acid phosphatase (TRAP), runt-related transcription factor 2 (RUNX2), and osteocalcin (OCN). DL, alone or in combination with adjunctive therapy to SRP in the treatment of experimental periodontitis, resulted in a decreased local inflammatory response. At 7-days posttreatment, the DL and SRP/DL groups had fewer TRAP-positive cells and more RUNX2-positive cells. There was greater OCN immunolabeling in the DL group than in the C and SRP groups at 15 days. There was less ABL in the DL and SRP/DL groups at 15 and 30 days. In conclusion, DL was effective in the treatment of ligature-induced periodontitis in rats, both when used alone and when used as adjunctive therapy to SRP.
Keywords: Periodontitis; Alveolar bone loss; Lasers; Rats